Palaeodemographic changes in the Tiszántúl in the 10th–13th century - Jánosi, István; Szathmáry, László (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
Craniometrical and anatomical investigations discovered that the structure of the populations living in the Alföld region (Hungary) might be quite different between the age of the Hungarian conquest (10th century) and the Arpadian age (11th–13th century). This statement was presumed on the basis of skeletons derived from cemeteries dating from both the age of the Hungarian conquest and the Arpadian age. Considering the above mentioned thoughts, the basic aim of this study was to perform comparative palaeodemographic analysis on representative 10th and 11th–13th skeletal populations excavated from cemeteries in the Tiszántúl region. During the analysis, the samples were separated into two groups according to the archaeological periods (the age of the Hungarian conquest and the Arpadian age). It was observable that the 10th century populations showed great variation in the mortality parameters. Uniform characteristic could not be noticed in the Tiszántúl region. Contrarily, the Arpadian age populations, especially dating from the 11th century showed much more homogeneous demographic profile as compared with that of the cemeteries from the 10th century (the age of the Hungarian conquest). Among the 11th century populations, much lesser difference could be detected than that among the 10th century samples. It is quite feasible that the 10th century populations composed of various ethnic groups of different origin have settled in the Carpathian basin according to the natural environment. It presumably caused territorial isolation. However, in the 11th century, the differences between groups of people could not be detected clearly, possibly due to certain political intentions of King Saint Stephen which resulted in population homogenization in the Arpadian age.